Qualidade de vida, fatores sociodemográficos, clínicos e subjetivos em adultos com feridas de difícil cicatrização - Jacon, João Cesar (2024)
To assess the quality of life and sociodemographic, clinical, and subjective factors (depression, anxiety, stress, self-esteem, self-efficacy, self-care, and pain) in adults with hard-to-heal wounds. Methodology: A correlational, descriptive, cross-sectional study with a quantitative approach. Data were collected in two municipalities in the state of São Paulo. The sample consisted of 116 patients. The following instruments were used to collect the data: the Depression, Anxiety and Stress Scale - Short Form (DASS-21), the Appraisal of Self-Care Agency Scale (ASA-A), the Rosenberg Self-Esteem Scale (RAS), the Perceived General Self-Efficacy Scale (The General Self-Efficacy Scale) and the Freiburg Life Quality Assessment-Wound (FLQA-Wk), by which the results were presented considering relative and absolute frequencies, as well as measures of central tendency. For inferential statistical analysis, the following tests were used: correlation (Spearman and Chi-square), association and comparison (Mann-Whitney or Kruskal Wallis), and the Bonferroni post-test. CAAE: 63323822.9.0000.5504. Results: DASS-21, depression (68.1%), anxiety (76.7%), and stress (71.6%) between normal and mild, 43.1% optimal abilities to carry out self-care. 50% of the patients reported pain in the wound during the interview, with a median of 1.0 (IIQ 0-8.0), and the median time the wound had existed was 52 months (IIQ 17.0-204.0). In the quality-of-life assessment, the median was 10.7 (IIQ 6.4–13.6), the psychological well-being domain represents a state of a better quality of life (median 1.0 and IIQ 0.3–1.5), and the daily life (median 2.4 and IIQ 1.4–3.2) and treatment (median 2.4 and IIQ 1.5–3.0) domains represent domains with the worst quality of life. The overall score for self-esteem was a median of 31.5 (IIQ 26.0–34.8) and for self-efficacy, a median of 4.3 (IIQ 3.2–4.8). Conclusion: Patients with difficult-to-heal wounds had a poor overall quality of life and were associated with the presence of pain at the time of the interview, female gender, insufficient income, not practicing physical activity, and wounds of vasculogenic etiology, as well as symptoms of moderate depression. Wound pain during the interview was correlated with the number of wounds that were difficult to heal and was associated with symptoms of mild depression. Patients with vasculogenic wounds complained of greater intensity. Symptoms of moderate depression were identified in single people, and low schooling was associated with depressive symptoms. Anxiety, depression, stress, low self-esteem, and a low perception of self-efficacy were more evident in women with wounds that were difficult to heal. Physical activity and schooling had a negative influence on perceived self-efficacy. Elderly people with chronic wounds have a lower capacity for self-care, lower self-esteem, and a poorer perception of self-efficacy.